Is Input Utilization Inelastic to Coffee Production - Nurhapsa Nurhapsa; Andi Nuddin; Suherman Suherman; Betrixia Barbara (International Journal of Agriculture System, 2020)
The agricultural sector is one of the important sectors for the Indonesian economy. Coffee is one of the commodities produced from the plantation sub-sector included in the agricultural sector which also contributes greatly to the Indonesia economy, especially as a source of foreign exchange, employment and income sources as well as other economic actors. This study aims to determine whether the factors of land area production, number of productive trees, farming costs and labour used by coffee farmers are elastic or inelastic to coffee production. Samples were taken as many as 400 coffee farmers spread in four districts namely North Toraja Regency, Enrekang Regency, Sinjai Regency and Bantaeng Regency, South Sulawesi, Indonesia. Data collected in the form of primary data and secondary data. The analysis used the Cobb-Douglass production function. The results show that the use of production factors; land area, number of productive trees, farming costs and labor are inelastic to coffee production, the scale of farming follows the rules of increasing return to scale. Therefore, it is expected that the support of local government (related institutions) to assist coffee farmers in providing superior seeds to increase coffee production, farmers incomes and reduce land conversion.